Isolated Non-Compaction of Right Ventricular Myocardium, A Rare Congenital Anomaly and Role of Echocardiogram: A Case Report - Sudeb Mukherjee; SC Mandal (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2020)
The ventricular non-compaction or spongy myocardium is a rare congenital cardiomyopathy which is caused by defective morphogenesis of myocardium during embryonic life. It is characterised by excessive, coarse trabeculations within ventricular myocardium beyond papillary muscle insertion which communicates freely with the ventricular cavity. This carries high risk for development of serious arrhythmia, thromboembolic stroke, pump failure etc. Isolated LV involvement is the most common presentation (68%) and biventricular involvement is the next most common presentation (22-38%). Isolated non-compaction of RV myocardium is a rare anomaly. We are hereby presenting such a case.